Kearifan Lokal Batak Toba Dalam Mendukung Sektor Pariwisata di Kabupaten Samosir - Dumora Jenny Margaretha Siagian (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2018)
This study aims to explore and analyze the local wisdom of Batak Toba community that is useful and can support the tourism sector in Samosir regency. As a beautiful island occupied by generally ethnic Batak Toba, Samosir not only has beautiful natural scenery, but also has a culture and local wisdom that can attract tourists to learn it. However, Samosir has not become a comfortable tourist destination for tourists, especially for those who were initially interested in the Toba Batak culture. This research is a qualitative research which describes descriptively local wisdom of Toba Batak society that can be rebuilt to attract tourists to visit Samosir Island. Data collection is done through observation, interview, and trace of documents and previous research results. The analysis is done descriptively. The result of research is that Batak Toba local wisdom becomes an important potential in shaping the character of Batak people who can socialize with tourists. So that the tourists can be comfortable in the midst of indigenous peoples. So local wisdom needs to be revived and re-empowered, in addition to welcoming tourists, as well as to preserve the local wisdom that the ancestors have taught to be guided by the next generations. This can be done through education and socialization to schools and community groups around the tourist attraction. Recommendations that can be given are the need for coordination between government and traditional leaders in inventoring, revitalizing and developing local wisdom for students in schools and communities around tourism objects that can support the tourism sector. Keywords: local wisdom; culture; Batak Toba; tourism; Samosir